Leadership Style of the Head of Religious Affairs Office in Fostering Employee Discipline: An Islamic Education Perspective - Nasir, Iqbal; Tahir, Muhyiddin; Akbar, Baso (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study explores the methods used by the Head of the Office of Religious Affairs in Wawo Subdistrict to foster employee discipline through an Islamic Religious Education perspective. Employing a qualitative, descriptive field study approach, data was collected through interviews, observations, and documentation. The analysis utilized deductive reasoning, moving from general findings to specific conclusions. The results indicate that the head’s leadership style is predominantly democratic, tailored to the existing situational and organizational conditions. Discipline is nurtured through a family-oriented approach, with employees actively involved in various training programs aimed at enhancing their skills and service quality. Key factors influencing employee discipline include the provision of appropriate compensation, implementation of warnings, and exemplary leadership behavior. Leadership by example emerges as a vital element in fostering discipline, enabling the creation of a professional, responsible workforce capable of serving the community effectively. This study highlights the significant role of leadership styles and strategies in building a disciplined and competent team within the context of the Office of Religious Affairs, offering practical insights for leadership development in similar institutions.